Lekcja Barańczaka. "Nieufni i zadufani" po latach - Woźniak-Łabieniec, Marzena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The aim of this article is to analyze the reception the book of Stanisław Barańczak about classicism and romanticism in the poetry of the sixties. This book show linguistic trend in Polish poetry. It is important to ask: how distinguished the author by the opposition “dialectical Romanticism” (poetry linguistic) and classicism (inspired by Eliot) influenced subsequent synthesis of critical and what is its impact on subsequent generations of the poets, especially poetry of artists born in the sixties.